The Influence of Competence and Work Discipline on Employee Performance at Bank Jatim Surabaya Branch - Sumiati (Journal of Management, 2025)
This study aims to analyze the influence of competence and work discipline on employee performance at Bank Jatim Surabaya Branch. The research was motivated by the fact that in the increasingly competitive banking industry, human resources play a crucial role in ensuring service quality and organizational performance. Competence, which includes knowledge, skills, and attitudes, and work discipline, which reflects employees’ adherence to organizational rules and responsibilities, are believed to be key determinants of performance.The study employed a quantitative associative approach, involving 50 employees selected through purposive sampling. Data were collected using questionnaires and documentation, and analyzed through multiple linear regression, t-test, F-test, and coefficient of determination (R²). The findings revealed that both competence and work discipline have positive and significant effects both partially and simultaneously on employee performance. The regression results show that competence contributes more strongly to performance (β = 0.412) compared to work discipline (β = 0.367). The F-test value of 24.57 with a significance of 0.000 (< 0.05) indicates that both independent variables jointly influence performance, while the coefficient of determination (R² = 0.61) suggests that 61% of performance variation is explained by competence and work discipline.These results confirm that competent and disciplined employees tend to deliver better service, achieve performance targets, and maintain operational accuracy critical aspects in the banking sector. Therefore, it is recommended that Bank Jatim management strengthen training programs to enhance employee competence and consistently enforce discipline to sustain high levels of performance and service excellence.